Postponement Strategies in Supply Chain Management - Cheng, T. C. Edwin; Li, Jian.; Wan, C. L. Johnny; Wang, Shouyang; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Within supply chain management (SCM), postponement is a deliberate action to delay final manufacturing or distribution of a product until receipt of a customer order. This reduces the incidence of wrong manufacturing or incorrect inventory deployment. Postponement strategies and practices serve to reduce the anticipatory risk in a supply chain. It can be fine-tuned or staged so that only the generic parts shared by a firm$1 (Bs various end products are warehoused, used only once orders come in for whichever products are selling, and will reduce inventory pressures throughout the firm. Despite much existing research in the area, no one book devoted solely to postponement has been published. At its core, Postponement Strategies in Supply Chain Management analyzes how both pull postponement strategy and form postponement strategy can be leveraged to yield substantial benefits to adopting firms in different competitive environments. The book is intended for researchers in supply chain management interested in conducting in-depth studies on postponement strategies. It is also intended for practitioners trying to understand the workings of postponement strategies and looking for guidance and decision support for the implementation of postponement strategies. Therefore, the book can be useful not only for researchers but also for practitioners and graduate students in operations management, management science, and business administration.s
Analysis of Pull Postponement by EOQ-based Models -- Analysis of Postponement Strategy by EPQ-based Models -- Evaluation of a Postponement System with an (r, q) Policy -- Simulation of a Two-End-Product Postponement System -- Application of Postponement: Examples from Industry -- Conclusions, Implications and Future Research Directions.
Keywords: Economics; Industrial engineering; Operations research; Economics/Management Science; Operation Research/Decision Theory; Production/Logistics/Supply Chain Management; Industrial and Production Engineering